CRISPR-Cas9: Revolutionizing the Genetic Frontier - Ms. Khushi Yuvraj Patil; Mr. Akash S. Jain; Mr. Divakar R. Patil; Mr. Azam Z. Shaikh; Mr. Sameer Shaikh; Dr. S. P. Pawar (International Journal of Genetic Modifications and Recombinations, 2025)
The rapid development of CRISPR/CRISPR-associated enzyme (Cas) technology has enabled truly customised treatment of human genetic disorders, paving the way for recent developments in the field of gene therapy. Because CRISPR/Cas can accurately target and edit individual genes within a genome, it has established itself as a formidable tool for genetic manipulation. CRISPR/Cas9 technology allows for precise editing of specific DNA sequences in an organism's genome. This method uses three key components: the target DNA, a guide RNA that directs the editing machinery to the correct location, and the Cas9 enzyme, which makes a cut at the desired site in the DNA. This two-component system, consisting of the guide RNA and Cas9 enzyme, provides an efficient and straightforward approach to gene editing. CRISPR/Cas9 is becoming into a potent tool for high throughput target gene screening in cancer treatment. Genome editing using CRISPR/Cas9 technologies has becoming more and more popular. Building on these foundational principles, CRISPR/Cas9 technology has rapidly evolved to become a cornerstone in the study and treatment of genetic diseases. Its ability to precisely target DNA sequences enables researchers to correct mutations that cause hereditary disorders, offering hope for cures where none previously existed. Beyond its therapeutic applications, CRISPR is widely used in basic research to understand gene function and regulation. Scientists employ this tool to knock out or modify genes in various organisms, which accelerates discoveries in biology and medicine. Moreover, the simplicity and cost-effectiveness of CRISPR/Cas9 compared to previous gene-editing technologies have democratized genetic engineering, making it accessible to a broader range of laboratories worldwide. This democratization has led to an explosion of innovative research and clinical trials exploring new ways to combat diseases such as cancer, HIV, and genetic blindness. Despite these advances, ethical and safety considerations remain critical in the development and application of CRISPR technology. Researchers are actively working to refine the specificity of CRISPR/Cas9 to minimize off-target effects and ensure long-term safety in patients. As these challenges are addressed, CRISPR’s potential to revolutionize medicine and biotechnology continues to grow exponentially, promising a future where genetic diseases can be precisely treated or even prevented altogether.
Keywords: CRISPR; Gene therapy; HDR pathway; NHEJ pathway; iPSCs